Letter: comparison of clinical prediction rules for ruling out cirrhosis in non‐alcoholic fatty liver disease (NAFLD). Issue 6 (22nd August 2022) - Shiha, Gamal; Mikhail, Nabiel; Soliman, Reham
Abstract : LINKED CONTENT This article is linked to Brandman et al papers. To view these articles, visit https://doi.org/10.1111/apt.16874